Optical stark effect on CdSe nanoplatelets with mid-infrared excitation for large amplitude ultrafast modulation. (11th June 2023) - Diroll, Benjamin T
Abstract: The optical Stark effect is a universal response of the electronic structure to incident light. In semiconductors, particularly nanomaterials, the optical Stark effect achieved with sub-band gap photons can drive large, narrowband, and potentially ultrafast changes in the absorption or reflection at the band gap through excitation of virtual excitons. Rapid optical modulation using the optical Stark effect is ultimately constrained, however, by the generation of long-lived excitons through multiphoton absorption. This work compares the modulation achievable using the optical Stark effect on CdSe nanoplatelets with several different pump photon energies, from the visible to mid-infrared. Despite expected lower efficiencies for spectrally-remote pump energies, infrared pump pulses can ultimately drive larger sub-picosecond optical Stark shifts of virtual excitons without creation of real excitons. The CdSe nanoplatelets show subpicosecond shifts of the lowest excitonic resonance of up to 22 meV, resulting in change in absorption as large as 0.32 OD (49% increase in transmission), with a long-lived offset from real excitons less than 1% of the peak signal.